Retail investors' perspective on ESG investments - Thomas Heidorn; Timo Watermeyer; Patrick Haar (Frankfurt School of Finance & Management, 2023)
Retail investors are an essential group in shaping the effects of ESG investing and ESG assets under management are growing at an exponential rate. This study of retail investors' demand generates first evidence on their ESG-relevant decisions. In general, ESG was regarded as a highly interesting topic by retail investors, indicating that its role in financial decisions will further increase in the future. In practice, the portfolio of companies chosen to represent ESG values varies substantially across different funds. We found that, for most retail investors, ESG values have a meaningful relationship with each other. Nevertheless, there is no general agreement on how to fulfil these values. Only few relationships between specific ESG values and measures of achieving ESG values (MAVs) were determined. Moreover, no relationships were found between MAVs and indirect ESG values. Nevertheless, some MAVs had reliable relationships with each other and could be ranked according to controversiality, indicating that MAVs could be clustered for optimal representation of retail investor preference groups. Most retail clients prefer a financially optimal investment, but a meaningful group would accept lower performance to support their values. This confirms additional non-financial utility of investment decisions: Association or dissociation with certain ESG values.
Keywords: G11; G24; G32; Q56; 330; ESG; ESG funds; retail investors; ESG investment; measures achieving values; ESG survey